Greater relative first and second lactate thresholds in females compared with males: consideration for exercise prescription - Benítez-Muñoz, J. A.; Rojo-Tirado, M. Á.; Benito Peinado, P. J.; Murias, J. M.; González-Lamuño, D.; Cupeiro, R. (International Journal of Sports Physiology and Performance, 2025)
Purpose To investigate differences between females and males at lactate thresholds 1 (LT1) and 2 (LT2).